Depressive and Aggressive Responses to Frustration: Development of a Questionnaire and Its Validation in a Sample of Male Alcoholics. (17th March 2011) - Baars, M. Y.; Müller, M. J.; Gallhofer, B.; Netter, P.
Abstract : Since clinical and biochemical observations point to much overlap between depression and aggression, both characterised by intolerance to frustration, a questionnaire was developed to test if different patterns of depressive and aggressive reactions elicited by exposure to negative events and deprivation from expected positive ones in human and nonhuman conditions, respectively, would result in specific response patterns in depressive and aggressive persons. The questionnaire was tested for internal consistency in a pilot healthy sample and for correlations of responses with the personality factors of Aggression and Depression in 60 abstinent male alcoholics. Aggressive and depressive responses were highly correlated across all stimulus conditions, and not specifically but rather equally associated with the personality factors of Aggression and Depression, confirming the close association between these dimensions.